2022
DOI: 10.1111/jpn.13759
|View full text |Cite
|
Sign up to set email alerts
|

The risk assessment of high‐fat diet in farmed fish and its mitigation approaches: A review

Abstract: In the era of intensification of fish farms, the high‐fat diet (HFD) has been applied to promote growth and productivity, provide additional energy and substitute partial protein in fish feeds. Certainly, HFD within specific concentrations was found to be beneficial in boosting fish performance throughout a short‐term feeding. However, excessive dietary fat levels displayed vast undesirable impacts on growth, feed efficiency, liver function, antioxidant capacity and immune function and finally reduced the econ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(18 citation statements)
references
References 143 publications
0
18
0
Order By: Relevance
“…Similarly, previous studies revealed the polyphenols-mediated beneficial effects on intestinal tight junction formation and barrier function [ 56 , 57 ]. The studies stated that polyphenols could enhance the integration of the intestines via different mechanisms [ 58 , 59 ]. Dietary P. australis is rich in polyphenols that can increase the expression of claudin-3 and claudin-7, leading to magnified intestinal integrity.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, previous studies revealed the polyphenols-mediated beneficial effects on intestinal tight junction formation and barrier function [ 56 , 57 ]. The studies stated that polyphenols could enhance the integration of the intestines via different mechanisms [ 58 , 59 ]. Dietary P. australis is rich in polyphenols that can increase the expression of claudin-3 and claudin-7, leading to magnified intestinal integrity.…”
Section: Discussionmentioning
confidence: 99%
“…As aquaculture grows increasingly important for feeding the world's expanding population, so do the natural resources necessary to generate aquaculture feed ingredients [3]. Tilapia are warm-water fish with a light flavor, high yield, and tolerance to poor water quality [4][5][6]. Economically, Nile tilapia is one of the most significant freshwater fish species.…”
Section: Introductionmentioning
confidence: 99%
“…With the fast development of aquaculture, high-fat diets are widely utilized because they promote growth and protein retention [ 6 ]. However, excessive lipids can cause various metabolic diseases [ 7 , 8 ] such as metabolic disorders, fat accumulation, inflammation and endoplasmic reticulum stress [ 9 , 10 , 11 ], which can affect fish health.…”
Section: Introductionmentioning
confidence: 99%
“…Many factors, such as species, growth stage and environment, can regulate the gut microbial community [ 16 ]. It is universally recognized that diet plays a key role in determining the composition of the gut microbiota and that dietary lipid levels influence the metabolic capacity of the gut microbial community [ 11 , 17 ]. However, as the freshwater drum is a newly domesticated aquatic animal, the effects of a high-fat diet on its gut and microbiota have not been studied.…”
Section: Introductionmentioning
confidence: 99%